Anatomical Characteristics and Variations of Thoracic Segmental Arteries With 3-Dimensional CT Analysis. Issue 22 (15th November 2022) - Yamada, Yohei; Demura, Satoru; Kato, Satoshi; Shinmura, Kazuya; Yokogawa, Noriaki; Handa, Makoto; Annen, Ryohei; Kobayashi, Motoya; Nagatani, Satoshi; Tsuchiya, Hiroyuki
Abstract : Study Design: Observational study using retrospective contrast-enhanced computed tomography (CT) analysis. Objective: This study aimed to investigate the anatomical characteristics and variations of the thoracic segmental arteries. Summary of Background Data: Few cadaver studies of segmental arteries to the thoracic spine have been reported; however, no previous studies have reported the use of contrast-enhanced CT in the upper to middle thoracic spine. Detailed anatomical information of the thoracic segmental arteries is essential to avoid vascular injuries in thoracic spine surgery, such as in the anterior and posterior approaches and minimally invasive surgery. Materials and Methods: Patients who underwent CT angiography of the thoracic spine between 2012 and 2021 were retrospectively analyzed. The pathways of the thoracic segmental arteries were reviewed. Anatomical differences depending on the vertebral level and right/left segmental arteries were investigated. Results: Thirty-one patients (15 men and 16 women; mean age 55.8 yr) with 591 segmental arteries were surveyed. The distribution of segmental arteries differed depending on the vertebral level, which ran more longitudinally in the upper thoracic region and transversely in the lower thoracic region. Common trunks were frequently observed in the segmental arteries of T3-5. Segmental arteries frequently crossed the disks in the right anterior and left middle areas of the thoracic spine, whereas in the T4/5 disks, segmental arteries crossed the disks over a wide area. The presence of multiple segmental arteries within a single vertebra was higher at the T5-7 vertebral level. Conclusion: The distribution of the segmental arteries was asymmetrical and varied depending on the vertebral level. In the upper to middle thoracic, segmental arteries ran at every position of the vertebral body due to their longitudinal nature and the presence of multiple segmental arteries within a single vertebra, especially in T5-7. The results of this study provide critical information for thoracic spine surgery.